Atomic spectrometry update – a review of advances in environmental analysis. Issue 1 (6th November 2020) - Bacon, Jeffrey R.; Butler, Owen T.; Cairns, Warren R. L.; Cavoura, Olga; Cook, Jennifer M.; Davidson, Christine M.; Mertz-Kraus, Regina
Abstract : This review covers advances in the analysis of air, water, plants, soils and geological materials by a range of atomic spectrometric techniques including atomic emission, absorption, fluorescence and mass spectrometry. Abstract : In the field of air analysis, highlights within this review period included: new isotopic data for reference dust materials; a new device for preparing and mounting delicate air filter samples for X-ray analysis and use of oxygen-mediated mass-shift ion chemistry for measuring sulfur in aerosol samples by ICP-MS. The use of DGT and ionic liquids for preconcentrating trace elements and other analytes from waters has become more established. The resurgence of interest in As speciation has been noted with extensive reviews as well as methods for the challenging determination of thioarsenic species. Improvements in methodologies have achieved LODs with GC-MS that were once only possible with ICP-MS, thereby making it possible for a larger number of laboratories to undertake speciation analysis. Field preconcentration methods and hand-held XRF instruments have made it easier to screen contaminated waters, thereby allowing sampling sites to be selected more effectively. There has been renewed interest in atomic emission sources such as the arc, GD and plasmatron for the analysis of plants and soils. The upward trend in publication of LIBS methods continued but many lacked validation through comparison with established methods or analysis of CRMs. There is a clear need for closer collaboration between the physicists driving fundamental developments in plasma spectroscopy and analytical geochemists, who understand the complexities of environmental samples and the requirement to implement robust QC procedures. Interest in multivariate analysis of pXRFS spectra to predict soil properties related to fertility has increased. Much research effort continues to be devoted to characterisation of matrix-matched geological RMs, both synthetic and natural samples, particularly for in situ analysis by microanalytical techniques, such as LA-MC-ICP-MS and SIMS. Such RMs are essential to compensate for matrix effects and need to be available in sufficient quantities to enable interlaboratory comparisons based on the same RM. The increased access to MC-ICP-MS instrumentation, especially in China, is reflected in the diverse range of isotopic systems now being studied. Most studies present incremental improvements to existing separation procedures or measurement protocols.